YESUS KRISTUS SEBAGAI JURUSELAMAT: SEBUAH INTERPRETASI KITAB MAZMUR 23 - Gulo, Syutriska Kardia (Fides et Ratio : Jurnal Teologi Kontekstual Seminari Tinggi St. Fransiskus Xaverius Ambon, 2024)
Life is often ambiguous, and many people struggle with various problems. Psalm 23 is a familiar biblical text that describes God as a shepherd who nurtures and saves His people. The purpose of this writing is to understand the theological meaning of Psalm 23, where the Lord Jesus guides the way of life for His people. The author supports their discussion with related books and journal articles. The use of this method aims to clarify the author's intent and purpose for the reader. This article employs a text analysis approach to examine the Lord Jesus as the good shepherd, who is capable of ruling over all creation and serving as a bridge for individuals to overcome life's challenges.